Clemastine Ameliorates Perioperative Neurocognitive Disorder in Aged Mice Caused by Anesthesia and Surgery - Wensi Wu; Xiaojun Zhang; Jiaxin Zhou; Hongmei Yang; Junjun Chen; Le Zhao; Junying Zhong; Wei-jye Lin; Wei-jye Lin; Zhi Wang (Frontiers Media S.A., 2021)
Perioperative neurocognitive disorder (PND) leads to progressive deterioration of cognitive function, especially in aged patients. Demyelination is closely associated with cognitive dysfunction. However, the relationship between PND and demyelination remains unclear. Here we showed that demyelination was related to the pathogenesis of PND. Clemastine, an antihistamine with potency in remyelination, was predicted to have a potential therapeutic effect on PND by next-generation sequencing and bioinformatics in our previous study. In the present study, it was given at 10 mg/kg per day for 2 weeks to evaluate the effects on PND in aged mice. We found that clemastine ameliorated PND and reduced the expression levels of inflammatory factors such as tumor necrosis factor alpha (TNF-α) and interleukin-1 beta (IL-1β). Further investigation suggested clemastine increased the expression of oligodendrocyte transcription factor 2 (OLIG2) and myelin basic protein (MBP) to enhance remyelination by inhibiting the overactivation of the WNT/β-catenin pathway. At the same time, the expression of post-synaptic density protein 95 (PSD95, or DLG4), brain-derived neurotrophic factor (BDNF), synaptosomal-associated protein 25 (SNAP25) and neuronal nuclei (NEUN) were also improved. Our results suggested that clemastine might be a therapy for PND caused by anesthetic and surgical factors in aged patients.